View of Vicksburg and plan of the canal, fortifications & vicinity - Wrotnowski, L. A. (1863)
Scale 1:63,360.; LC Civil War Maps (2nd ed.), 294; Description derived from published bibliography.; Indicates fortifications, location, type and names of boats, roads, railroads, levees, drainage, vegetation, and the names of a few residents.; Inset: [View of Vicksburg] 17 x 54 cm.; Available also through the Library of Congress web site as raster image; Inscribed in the lower right hand corner "Major David C. Houston, Chief Engineer, 19th Army Corps, with the compliments from the author."